The fossil record of the genus Varanus from the Southern Caucasus (Armenia, Georgia) - Vasilyan, Davit (PeerJ, 2020)
The Southern Caucasus, with its special geographic position and complex topography, is a well-known biodiversity hotspot. However, the formation of this hotspot remains largely unstudied. To reveal this, a thorough study of the fossil record of the region is necessary. In the present paper, we describe for the first time fossil monitor lizards (Varanus sp.) from two late Miocene localities from the Southern Caucasus (Jradzor, Armenia and Tetri Udabno, Georgia). We suggest that both fossils belong to a small-sized monitor lizard, comparable to the present-day species found in Iran and the Middle East (e.g., Iraq, Saudi Arabian)—the most western part of the extant monitor lizards’ Eurasian distribution range. Our finds show that the genus had a broad distribution in the Eastern Paratethyan region during the late Miocene. In addition, we provide the probable temperature ranges for fossil localities.